Baculovirus synergism for improved management of false codling moth Thaumatotibia leucotreta Meyr. (Lepidoptera: Tortricidae) - Taylor, David Graham (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Baculoviruses are an environmentally friendly and effective agent for managing lepidopteran pests. This includes the management of Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae), a serious pest of citrus in Southern Africa and a major threat to the South African citrus export industry. For more than 15 years, CrleGV-SA- based biopesticides have been used as part of an integrated pest management strategy for the control of T. leucotreta in citrus orchards in South Africa, under the names Cryptogran™ and Cryptex®. While these biopesticides have been effective during this period, there are some areas in which baculovirus use could potentially be improved. Baculoviruses are notoriously slow to kill in comparison to chemical-based pesticides, and lately, pest resistance to baculoviruses has become a major concern with the development of resistance by Cydia pomonella (Linnaeus) (Lepidoptera: Tortricidae) to its granulovirus occurring in the field in Europe. The consistent use of CrleGV-SA for more than 15 years in the field has raised concern that T. leucotreta could develop resistance to this virus, and has made it necessary to alter baculovirus-based management strategies to prevent this from occurring. A second baculovirus, Cryptophlebia peltastica nucleopolyhedrovirus (CrpeNPV), has recently been isolated and was shown to be effective against T. leucotreta. However, the interactions between CrleGV-SA and CrpeNPV are not yet understood and so it is important to test these interactions before both viruses are applied on the same orchards. Not only is it important to know whether these viruses could negatively impact each other, but it is also important to test whether they could interact synergistically. A synergistic interaction could not only provide a potential tool for the management of resistance, but it could also be exploited to improve baculovirus-based management of T. leucotreta. In this study, a stock of CrleGV-SA was purified by glycerol gradient centrifugation from T. leucotreta cadavers, while a stock of CrpeNPV purified from Cryptophlebia peltastica (Meyrick) (Lepidoptera: Tortricidae) cadavers was provided by River Bioscience (Pty) Ltd. These stocks were screened for purity by a multiplex polymerase chain reaction (mPCR) protocol designed to detect CrleGV-SA and CrpeNPV. The occlusion body (OB) density was then calculated using darkfield microscopy and a counting chamber. Both stocks were shown to be pure within the limits of the mPCR protocol, and the CrleGV-SA and CrpeNPV stocks were calculated to contain 3.08 × 1011 OBs/mL and 1.92 × 1011 OBs/mL respectively The first aspect of the interaction between CrleGV-SA and CrpeNPV that was investigated was the dose mortality, in terms of lethal concentration. This was calculated using 7-day surface-dose biological assays for each virus and a 1:1 mixture of OBs of the two against T. leucotreta neonates. The lethal concentrations of each treatment required to kill 50 % of larvae (LC50) and 90 % of larvae (LC90) for each treatment were then calculated and compared using a probit regression. The mixed infection performed significantly better than either virus by itself, while each virus by itself did not differ significantly from the other. The LC50 for CrleGV-SA, CrpeNPV and the mixed infection were 1.53 × 104 OBs/mL, 1.15 × 104 OBs/mL and 4.38 × 103 OBs/mL respectively. The LC90 of CrleGV-SA, CrpeNPV and the mixed infection were calculated to be 4.10 × 105 OBs/mL, 1.05 × 105 OBs/mL, and 4.09 × 104 OBs/mL respectively. The second aspect of the interaction between CrleGV-SA and CrpeNPV that was investigated was the speed of kill. A time-response biological assay protocol was created that allowed for effective observation of the larvae. This was then used to generate time-mortality data that were analysed by a logit regression function to calculate and compare the treatments at the time of 50 % larval mortality (LT50) and the time of 90 % mortality (LT90). Each virus by itself did not differ significantly from the other, while the mixed infection took significantly longer to kill 50 % and 90 % of the larvae, suggesting that there is competition for resources between viruses during the secondary, systemic phase of infection. The LT50 for CrleGV-SA, CrpeNPV and the mixed infection were 117.5 hours, 113.5 hours and 139.0 hours respectively. The LT90 for CrleGV-SA, CrpeNPV and the mixed infection were 153.2 hours, 159.3, and 193.4 hours respectively. Finally, the composition of OBs recovered from the cadavers produced by the time-response biological assays were investigated by mPCR. A method for extracting gDNA from OBs in neonate-sized T. leucotreta larvae is described. The presence of CrpeNPV along with CrleGV-SA was noted in 4 out of 9 larvae inoculated with only CrleGV-SA. The presence of CrleGV-SA as well as CrpeNPV was noted in all but one larva inoculated with only CrpeNPV, and both CrleGV-SA and CrpeNPV were noted in all but one larva inoculated with a 1:1 mixture of the two, with one larva only being positive for CrleGV-SA. This suggests either stock contamination or the presence of covert infections of CrleGV-SA and CrpeNPV in the T. leucotreta population used in this study. This is the second study to report an improved lethal concentration of a mixed infection of CrleGV-SA and CrpeNPV against T. leucotreta neonates, and the first study to report the slower speed of kill of a mixed infection of CrleGV-SA and CrpeNPV against T. leucotreta neonates. While the improved lethal concentration of the mixed infection is a promising step in the future improvement of baculovirus-based biopesticides, it is at the cost of a slower speed of kill.
Keywords: Baculoviruses; Cryptophlebia leucotreta; Cryptophlebia leucotreta -- Biological control; Biological pest control agents; Citrus -- Diseases and pests; Codling moth; Cryptophlebia peltastica nucleopolyhedrovirus (CrpeNPV)